The Potential Value of Prehabilitation for Preventing Delirium in Elective Surgery for Aneurysms of the Abdominal Aorta [Corrigendum] - Meulenbroek AL; Steyerberg EW; Janssen TL; van Mil SR; Faes MC; van der Laan L (Clinical Interventions in Aging, 2025)
Meulenbroek AL, Steyerberg EW, Janssen TL, van Mil SR, Faes MC, van der Laan L. Clin Interv Aging. 2024;19:51–55. Page 51, Abstract, Results section, last sentence, the text “Also, patients in the prehabilitation group had a small, non-significant decreased length of hospital stay (4 days) compared to the control group (5 days) (p=0.07)” should read “Length of hospital stay was significantly shorter after prehabilitation in both the total group (5 days in control, 4 days after prehabilitation, p=0.02, Mann–Whitney U-test) and in the EVAR group (4 days in control, 3 days after prehabilitation, p=0.001)”. The authors apologize for this error.